Microplastics contamination in Coban Kethak and its flow - Vidayanti Viky; Retnaningdyah Catur; Arisoesilaningsih Endang (BIO Web of Conferences)
This study aims to identify the distribution and frequency of microplastics in the sediment and water of Coban Kethak, a water source in the Malang, Indonesia. Recreation, recreation with sanitary facilities, durian plantation, and paddy fields were the four sites from where samples were taken, and each represented a distinct set of human-caused features. Wet peroxide oxidation and density separation procedures were used to extract microplastics, which were seen and identified using stereomicroscopy. PCA and clustering were analyzed using PAST software to identify the main patterns of variation in microplastic density among locations. This study found that microplastics, all smaller than 3 μm in size, were found in four different shapes: fibers, pieces, films, and microbeads. Microplastic concentrations in sediment (84 particles/100g) and water (68 particles/50L) were highest at the recreational location and lowest in the paddy field region (0 microplastic in sediment sample and 44 particles/50L in water sample, respectively). According to principal component analysis and cluster analysis, the study shows that microplastic contamination is associated with human activities, with recreational areas being the most affected. According to these findings, further study and targeted solutions are needed to decrease microplastic contamination in freshwater ecosystems, especially in places with heavy human activity.